Genomic epidemiology analysis of extremely drug-resistant tuberculosis in Shanghai, China - Xiaoyu Lu; Yuan Jiang; Yanping Liu; Junhong Chen; Yinglin Lao; Jing Li; Yangyi Zhang; Nan Li; Lili Wang; Chenlei Yu; Qi Ye; Wei Wei; et al. (Emerging Microbes and Infections)
Tuberculosis (TB), particularly extremely drug-resistant TB (EDR-TB), remains a significant public health concern worldwide. Understanding the transmission patterns and epidemiological characteristics of EDR-TB is vital for effective disease control. Between 1 January 2006 and 31 December 2018, we collected clinical M. tuberculosis strains in Shanghai, with whole-genome sequencing performed on 58 identified clinical EDR-TB strains. We analyzed EDR-related genetic mutations, conducted phylogenetic analyses, and examined bacterial and epidemiological factors that influence their transmission. Among these 58 EDR patients, 43.1% (25/58) were aged 45–64 years, with a median age of 51 years (interquartile range, IQR, 29–59 years). About two-thirds of the EDR-TB patients were residents. We observed a clustering rate of 44.8% (26/58) among EDR strains. Logistic regression analysis indicated a higher risk of recent EDR-TB transmission among the strains with the drug-resistant compensatory mutations. The primary mode of EDR-TB transmission in the study setting was recent, direct person-to-person spread of drug-resistant strains, as evidenced by high clustering rates and the presence of identical resistance mutations among clustered cases.